1998
DOI: 10.1128/jvi.72.11.8517-8524.1998
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Transcription Early in Infection

Abstract: We studied the accumulation kinetics of murine coronavirus mouse hepatitis virus (MHV) RNAs early in infection by using cloned MHV defective interfering (DI) RNA that contained an intergenic sequence from which subgenomic DI RNA is synthesized in MHV-infected cells. Genomic DI RNA and subgenomic DI RNA accumulated at a constant ratio from 3 to 11 h postinfection (p.i.) in the cells infected with MHV-containing DI particles. Earlier, at 1 h p.i., this ratio was not constant; only genomic DI RNA accumulated, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Although the present study and the previous study (16) established that negative-strand genomic RNA is a template for MHV subgenomic mRNA synthesis throughout the infection, these studies do not eliminate the possibility that MHV subgenomic mRNA is also synthesized from subgenomic negative-strand template RNA late in infection. A number of studies aimed to test whether positive-strand RNA synthesis occurs using subgenomic negative-strand template RNA in cells infected with coronaviruses (8,(12)(13)(14) and with arterivirus (15), yet did not provide direct evidence of positive-strand RNA elongation from the subgenomic-length negative-strand template.…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…Although the present study and the previous study (16) established that negative-strand genomic RNA is a template for MHV subgenomic mRNA synthesis throughout the infection, these studies do not eliminate the possibility that MHV subgenomic mRNA is also synthesized from subgenomic negative-strand template RNA late in infection. A number of studies aimed to test whether positive-strand RNA synthesis occurs using subgenomic negative-strand template RNA in cells infected with coronaviruses (8,(12)(13)(14) and with arterivirus (15), yet did not provide direct evidence of positive-strand RNA elongation from the subgenomic-length negative-strand template.…”
contrasting
confidence: 82%
“…Although the previous study using the column-purified genome-length RI (11) and the present study used different experimental approaches to examine the nascent RNAs in the genome-length RI, the data from these two independent studies indicated that MHV genome-length negative-strand RNA is the template RNA for subgenomic mRNA synthesis. We showed that negative-strand genomic RNA is the template for subgenomic mRNA synthesis early in infection (16). Our new data strongly support the idea that negative-strand genomic RNA is a template for subgenomic mRNA synthesis throughout the infection.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In the control group, the DBT cells were coinfected with helper MHV-A59 and UV-irradiated P2 sample. MHV RNA replication activities, but not transcription activities, were active very early in infection (An et al, 1998) therefore, we expected that MIGCAT genomic DI RNA replication, but not transcription, would start immediately after coinfection in the control group; we expected to see similar susceptibility to UV-light irradiation of MIGCAT subgenomic and genomic DI RNAs, because subgenomic-size MIGCAT DI RNA should be synthesized after replication of genomic MIGCAT DI RNA. Intracellular RNAs were extracted 7 h p.i.…”
mentioning
confidence: 98%
“…Mouse hepatitis virus (MHV) is one of the most well-characterized coronaviruses. After MHV infection, MHV RNA synthesis, which involves synthesis of a genome-length, negative-strand RNA template (2,4,42) and subsequent synthesis of seven, mature mRNA species (31), takes place in the cytoplasm. MHV particles, which contain three envelope proteins (S, M, and E) and an internal helical nucleocapsid, which consists of N protein and genomic RNA, buds from internal cellular membranes (25,37,61).…”
mentioning
confidence: 99%